Answer: (f-g)(2)=14
Step-by-step explanation:
(f – g) (-2) means the same as subtracting f(2) and g(2). Since we are given f(x) and g(x), we can use them to solve. There are two ways to solve. One is to find f(2) and g(2), and then subtract them. Another way is to do (f-g)(x), then plug in x=2. I will show both methods.
Method 1
f(2)=3(2)²+1 [exponent]
f(2)=3(4)+1 [multiply]
f(2)=12+1 [add]
f(2)=13
g(2)=1-(2) [subtract]
g(2)=-1
(f-g)(2)=13-(-1) [subtract f(2) and g(2)]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Method 2
(f-g)(x)=3x²+1-(1-x) [distribute -1]
(f-g)(x)=3x²+1-1+x [combine like terms]
(f-g)(x)=3x²+x
(f-g)(2)=3(2)²+2 [plug in x=2, exponent]
(f-g)(2)=3(4)+2 [multiply]
(f-g)(2)=12+2 [add]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Now, we know that (f-g)(2)=14. We confirmed this with both methods.
7/8 and 3/4
Both need to have same denominator so it would be 32, in this case because 8*4 is 32.
7/32+3/32=10/32 simplified to 5/16
Answer:
3k or 3000
Step-by-step explanation:
Answer:
![p^{4}](https://tex.z-dn.net/?f=p%5E%7B4%7D)
![m^{2}](https://tex.z-dn.net/?f=m%5E%7B2%7D)
![n^{2}](https://tex.z-dn.net/?f=n%5E%7B2%7D)
Step-by-step explanation:
collect like terms and multiply
(p×p×p×p)×(m×m)×(n×n)
I believe (a+b)^5 would be the answer